(untitled) (Journal of Economic Research & Business Administration, 2017)
In this article value of a financial analysis for the financial manager in modern conditions of development of economy is provided, and also the attention on automated systems of the financial and economic and managerial analysis of economic activity of the entity is concentrated. The greatest attention at the same time is paid to the «Finekanaliz»-2016 Version 8.0.165 program. «Finekanaliz» is a professional automated system of the complex financial and economic and managerial analysis of economic activity of an accounting entity. Main objective of this program – enhancement of a financial analysis of an accounting entity. Financial analysis – «Finekanaliz» represents a packet for automation of the managerial and financial and economic analysis of the organizations and entities. The program allows to perform periodic monitoring and financial analysis of an accounting entity, including also express-analysis, to constitute balance estimations, to model development of a financial situation, to constitute analytical notes, to develop programs of sanitation and the development strategy of the company.